Identification of Lanosterol Protein As a Cataract Drug Candidate with Campheserol and Its Derivatives Using Docking and HKSA Computational Methods - Ananta Adita Eka Putra; I Gusti Made Sanjaya (Universitas Negeri Medan, 2025)
As time goes by, technological development is becoming increasingly rapid. Many researchers, especially chemists, take advantage of this situation to advance their research. Furthermore, to support their research, it generally requires a significant amount of funding, because identifying a single compound necessitates numerous tools to determine whether it contains other compounds or their derivatives that can be used as potential drug candidates. Cataract drugs are not widely available in the world, therefore this article discusses cataract drugs. Docking computational methods and HKSA were used to identify a compound and its derivatives as drug candidates. The identified compound is campesterol and its derivatives. In the lanosterol protein, there are campesterol compounds and their derivatives that can be used for toothache medication. The results obtained through the HKSA process indicate that campesterol and its derivatives can be used as cataract medication.